(2nd version to make explicit my implicit assumptions about A, B and C, and the definitions of the non-logical constants "⊂" and "≡".)
Intuitively, the following modal argument seems valid to me and to other people. However, can it be formally proved valid? Or proved not valid?
∀x, ∀y, ∀z, ((x ⊂ y) ∧ (y ⊂ z) → (x ⊂ z))
∀x, ∀y, ((x ⊂ y) ∧ (y ⊂ x) → (x ≡ y))
◇(A ⊂ C)
◻(B ⊂ C)
∴ ◇(A ≡ B)
Or, in ordinary language, where "⊂" means set inclusion and "≡" means identity:
A, B and C exist
A may be some part of C
B is some part of C
Therefore, A and B may be the same part of C
I'm researching expressiveness of modal logic, i.e. to what extent modal logic can express the kind of assertions people make using some ordinary, informal language.
The particular relation identified in the argument here seems to divide the population into (mainly) two groups, and broadly equal in size, those who accept the argument as valid, those who do not. However, those who do not, appear for the moment unable to articulate a conclusive rationale in favour of invalidity.
The only substantial rationale for invalidity offered so far is to exhibit an interpretation of A, B and C which keeps both premises true but makes the assertoric version of the conclusion, i.e. "Therefore, A is the same as B", false.
However, I take this to be inconclusive since it doesn't preclude other interpretations of A, B and C that make true the assertoric conclusion "Therefore, A is the same as B". So, A and B may be the same. QED.
As I see it, there is nothing in the premises that implies that A and B are necessarily different. This in turn implies that they are possibly the same, which is the conclusion of the argument. QED.
Isn't that good enough?